2014
DOI: 10.1152/ajpgi.00221.2014
|View full text |Cite
|
Sign up to set email alerts
|

Infantile hypertrophic pyloric stenosis (IHPS): A study of its pathophysiology utilizing the newborn hph-1 mouse model of the disease

Abstract: Welsh C, Shifrin Y, Pan J, Belik J. Infantile hypertrophic pyloric stenosis (IHPS): A study of its pathophysiology utilizing the newborn hph-1 mouse model of the disease. Am J Physiol Gastrointest Liver Physiol 307: G1198 -G1206, 2014. First published October 30, 2014 doi:10.1152/ajpgi.00221.2014.-Infantile hypertrophic pyloric stenosis (IHPS) is a common disease of unknown etiology. The tetrahydrobiopterin (BH4)-deficient hyperphenylalaninemia-1 (hph-1) newborn mouse has a similar phenotype to the human cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…19 We previously showed that ROCK-2 is a key regulator of gastropyloric motor function early in life and the tissue protein content is reduced in newborn rodents. 7,23 As judged by the Western blot findings and the Y27632 inhibitory effect, the present data demonstrate that wall strain-dependent changes regulate the fundic muscle contraction potential via the ROCK-2 signaling pathway. Stretch-induced ROCK activation was reported in cardiomyocytes, alveolar epithelia, vascular, airway, and bladder tissues.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…19 We previously showed that ROCK-2 is a key regulator of gastropyloric motor function early in life and the tissue protein content is reduced in newborn rodents. 7,23 As judged by the Western blot findings and the Y27632 inhibitory effect, the present data demonstrate that wall strain-dependent changes regulate the fundic muscle contraction potential via the ROCK-2 signaling pathway. Stretch-induced ROCK activation was reported in cardiomyocytes, alveolar epithelia, vascular, airway, and bladder tissues.…”
Section: Discussionsupporting
confidence: 57%
“…In the gastrointestinal tract this pathway is physiologically required and reduced ROCK‐2 activation is associated with dysmotility . We previously showed that ROCK‐2 is a key regulator of gastropyloric motor function early in life and the tissue protein content is reduced in newborn rodents …”
Section: Discussionmentioning
confidence: 99%
“…The increased sphincter tone in infants with this condition is likely related to reduced pyloric tissue neuronal nitric oxide (NO) synthase (nNOS) expression (1) and the resulting lower NO generation (25,36,44). In the rodent model of this disease, we previously showed that increased pyloric sphincter tone is transiently present (47).…”
mentioning
confidence: 99%
“…For instance, idiopathic hypertrophic pyloric stenosis is present in 1–2 week old hph-1 mice, but completely regresses in adult life8. BH4 deficiency has also been linked to the idiopathic human condition, hypertrophic pyloric stenosis, through a mechanism based on nitric oxide synthase-dependent pyloric sphincter regulation8. Idiopathic hypertrophic pyloric stenosis in humans solely manifests in infants and if left untreated, the condition spontaneously resolves9.…”
mentioning
confidence: 99%